Analysis of soil drying incorporating a constitutive model for curling - Maedo, Michael (2020)
This paper focuses on the shrinkage behavior of soil specimens involving sand, kaolinite, and kaolinite/sand mixtures subjected to desiccation under controlled conditions. Both, free and restrained shrinkage conditions are studied. The experiments show that pure soils do not curl upon unrestrained shrinkage; however, (under the same conditions) kaolinite/sand mixtures exhibited a marked curling. Furthermore, the mixture with the higher sand content broke through the middle of the sample after displaying a significant curling. Soils subjected to restricted shrinkage developed cracks with slight curling. To simulate the observed behavior, a mechanical model able to reproduce the detachment of the soil sample from the mold is proposed in this work and implemented in a fully coupled hydro-mechanical finite-element code. It is concluded that suction and differential shrinkage are key factors influencing the curling behavior of soils. The proposed framework was able to satisfactorily explain and reproduce the different stages and features of soil behavior observed in the experiments.